Power Line Communication (PLC) impulsive noise mitigation: a review - Peter, Aiyelabowo O.; Ng, Chee Kyun; Noordin, Nor Kamariah (International Institute for Science, Technology & Education, 2014)
Power Line Communication (PLC) is a technology which transforms the power line into pathways for the conveyance of broadband data. It has the advantage for it can avoid new installation since the current installation used for electrical power can also be used for data transmission. However, this power line channel presents a harsh environment for data transmission owing to the challenges of impulsive noise, high attenuation, selective fading and etc. Impulsive noise poses a severe challenge as its Power Spectral Density (PSD) is between 10–15dB above background noise. For good performance of the PLC system, this noise must be mitigated. This paper presents a review of the techniques for the mitigation of impulsive noise in PLC which is classified into four categories, namely time domain, time/frequency domain, error correction code and other techniques. Time domain technique is a memoryless nonlinear technique where the signal's amplitude only changes according to a specified threshold without changing the phase. Mitigation of impulsive noise is carried out on the received time domain signal before the demodulation FFT operation of the OFDM. Time/Frequency technique is a method of mitigating impulsive noise on the received signal at both before FFT demodulation and after FFT demodulation of the OFDM system. Error correction code technique is the application of forward error correction code by adding redundancy bits to the useful data bits for detection and possibly correction of error occurring during transmission. Identifying the best performing technique will enhance the deployment of the technique while exploring the PLC channel capacity enhancement in the future. The best performing scheme in each of the category were selected and their BER vs SNR curves were compared with respect to the impulsive noise + awgn curve. Amongst all of these techniques, the error correction code technique had a performance that presents almost an outright elimination of impulsive noise in power line channel.